Delamination and tensile effect of fine z-binder reinforced on fiberglass/polyester composite for aerospace applications - Gaona Tiburcio, Citlalli; Lira Martínez, Manuel Alejandro; Gómez Avila, Marianggy; Jáquez Muñoz, Jesús Manuel; Baltazar Zamora, Miguel Ángel; Landa Ruiz, Laura; Nieves Mendoza, Demetrio; Estupiñan López, Francisco Humberto; Almeraya Calderón, Facundo (Intechopen, 2023)
Delamination propagation in laminated composite materials is a common issue that always concerns us when we consider composites for structural purpose. Many possible solutions have been studied; the most famous is the three-dimensional (3D) woven composites materials, which have promising interlaminar fracture resistance but at the cost of increasing density, which for aerospace industry is very important. In this chapter, mode 1 double cantilever beam (DCB) interlaminar fracture toughness tests according to the American Society for Testing and Materials (ASTM) D5528 standard were performed on composite specimens made of E-Glass Saertex 830 g/m2 Biaxial (+/−45°) with Sypol 8086 CCP polyester resin with orthogonal z-axis oriented yarn woven of 0.22 mm diameter nylon monofilament. Four specimens were made with a longitudinal distance between the warp binders of 0.5, 1, 1.5, and 2 cm, respectively. A tensile test according to the ASTM D3039 standard was performed to study how z-binder may affect tensile resistance. The results show a considerable increase in interlaminar fracture toughness, several stress concentrators have been created because of the new yarn and premature failure in the matrix.